Innovative schools and learning environments in Germany and Finland Research and findings of comparative approaches. Ideas of good and next practice - Trumpa, Silke; Kostiainen, Emma; Rehm, Isolde; Rautiainen, Matti (Waxmann, 2020)
In this book, innovations in the education system are discussed and exemplary developments and projects from Finland and Germany are compared. On the one hand, the focus is on current research results, while on the other hand, examples of good practice from both countries describe remarkable ways of implementation and provide creative suggestions for one's own educational work. These are based on the experience of ten years of international cooperation between two teacher-training university locations